2017
DOI: 10.1002/jhet.3002
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Unsymmetric Monosubstituted and Disubstituted Dinaphthothiophenes

Abstract: Dinaphthothiophenes (DNTs) are a class of compounds with potential uses in organic semiconductors and the synthesis of unsymmetric catalysts. Symmetrical or asymmetrical addition of functional groups to the DNT structure may be desired for steric bulk in binaphthyl catalyst synthesis or tuning the electronic properties of semiconductors. Thus, versatility of functional group addition is a great asset in DNT synthesis. Until now, no versatile and concise methods for the synthesis of unsymmetrically substituted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…This method to synthesize 2Se has been previously used to prepare dinaphthothiophenes and benzonaphthothiophenes. [ 28,34–36 ] The final step was oxidation of 2Se by mCPBA in DCM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This method to synthesize 2Se has been previously used to prepare dinaphthothiophenes and benzonaphthothiophenes. [ 28,34–36 ] The final step was oxidation of 2Se by mCPBA in DCM.…”
Section: Resultsmentioning
confidence: 99%
“…Selenides 1Se to 4Se and DBSe except for 2Se were synthesized according to the literature. [ 28,30–37 ] Compounds 1 to 4 , DBSeO, diphenyl selenoxide, and DBTO were synthesized by oxidizing 1Se to 4Se , DBSe, diphenyl selenide, and DBT, respectively. Selenoxide 3 used for all the experiments that had less than 10% isomer content.…”
Section: Methodsmentioning
confidence: 99%
“…Typically, the reaction is carried out in toluenewater with an inorganic base. [4,9,16,34] Although other solvents can be used as well (DMF, [35,36] dioxane, [37,38] or EtOH [33] ), it has been demonstrated that scope of boronic acids and thiophene substitution patterns is much more narrow. One notable exception is a method proposed by Varello et al [35] with catalysis by Pd(PPh 3 ) 4 in the presence of Na 2 CO 3 in DMF-water.…”
Section: Introductionmentioning
confidence: 99%
“…However, unsubstituted benzo[ c ]thiophene has never been isolated so far due to the instability in air, in contrast to unsubstituted benzo[ b ]thiophene. Nevertheless, some benzo[ c ]thiophene derivatives with substituents on the thiophene ring and/or the benzene ring such as 1,3-diarylbenzo[ c ]thiophenes, 8–12 5,6-disubstituted benzo[ c ]thiophenes 13 and 1,3,4,7- or 1,3,5,6-tetrasubstituted benzo[ c ]thiophenes 14–16 have been synthesized and their optical and electrochemical properties were investigated, although much less substituted benzo[ c ]thiophene derivatives have been reported than substituted benzo[ b ]thiophene derivatives. In particular, few 3,3′-disubstituted-1,1′-bibenzo[ c ]thiophenes as the 1,1′-dimer of bibenzo[ c ]thiophene have been developed by Cava, 17 Mohanakrishnan 18 and Ono et al , 19 and they revealed their synthetic methods and, optical and electrochemical properties, although there are no reports on the synthesis and physical properties of unsubstituted 1,1′-bibenzo[ c ]thiophene 1,1′-BBT ( Fig.…”
Section: Introductionmentioning
confidence: 99%